Management and pricing of electric energy in Brazil - Rocha, Jéssica Taveira da; Rodrigues Neto, Caroline Soares; Santos, Diego Resende; Vieira, Eric Caetano Maurício; Eugenio, Quéren Hapuque de Souza; Campos, Carlos da Mata (Brazilian Journal of Production Engineering, 2023)
The electricity sector is composed of electricity generators, transmitters, and distributors. The generator supplies energy to the entire electrical system.  The transmitter is where the energy is transported to the consumer centers and is responsible for managing the high voltage (HV) lines and is the bridge between the generators and the distributor. The distributor is an agent holding a federal concession or permission to provide the public service of electricity distribution allowing it to be delivered to the customer's residence, and is also responsible for managing the medium and low voltage (MV/LV) power grid. To regulate this sector, regulatory agencies for national public services emerged in the 1990s. The National Agency of Electrical Energy (ANEEL), an autarchy under a special regime linked to the Ministry of Mines and Energy, began its activities in December 1997, created to regulate the Brazilian electrical sector, through Law 9427/1996 and Decree 2335/1997.
Keywords: Tariffs; ANEEL; Regulations.